Microplastic pollution in the sediment of Jakarta Bay, Indonesia. Issue 1 (December 2021) - Azizi, A; Setyowati, W N; Fairus, S; Puspito, D A; Irawan, D S
Abstract: During the COVID-19 pandemic, the increased use of plastic for personal protective equipment (PPE), single-use plastic bags, and food packaging raised significant environmental concerns. This study aimed to investigate the shape, abundance, and type of microplastics in the sediment of Jakarta Bay, specifically Tanjung Priok, Ancol Beach, and Sunda Kelapa Port. Sediment was collected using an Ekman sediment grab sampler and was extracted using the density separation method. The microplastics were counted and categorized according to the shape under a microscope. The differences in microplastic abundance in three different stations were determined using a one-way ANOVA. The polymer of microplastics was identified using Fourier Transform Infra-Red (FTIR). The results show that the abundance of the microplastics from coastal sediment was highest in the Sunda Kelapa Port (45066.67 ± 5205.13 particle/kg dry weight), which is significantly different (p<0.05) from Tanjung Priok (40533.33 ± 2444.04 particle/kg dry weight) and Ancol Beach (34666.67 ± 2444.04 particle/kg dry weight). Fragments dominated the shape of microplastic in Tanjung Priok, Ancol Beach, and Sunda Kelapa Post, comprising 36%, 40%, 38%, respectively, followed by fiber, film, and pellet. The FT-IR tests indicated that polypropylene (PP), polyethylene (PE), polystyrene (PS), and polyamide are the most prevalent microplastic polymers.